2021
DOI: 10.1093/mnras/stab2881
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dust content of galactic haloes with Herschel – IV. NGC 3079

Abstract: We present the results from an analysis of deep Herschel far-infrared observations of the edge-on disk galaxy NGC 3079. The PSF-cleaned PACS images at 100 and 160 μm display a 25 × 25 kpc2 X-shape structure centered on the nucleus that is similar in extent and orientation to that seen in Hα, X-rays, and the far-ultraviolet. One of the dusty filaments making up this structure is detected in the SPIRE 250 μm map out to ∼ 25 kpc from the nucleus. The match between the far-infrared filaments and those detected at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…The boundary of such a bubble may be related to the Xshaped structures centred on the nucleus, but with footpoints at a galactocentric radius r 0 . Thus then would define the midplane flow radius, which may be the boundary of this outflow (Veilleux et al 2021, see also Fig. 21).…”
Section: Motivationmentioning
confidence: 99%
“…The boundary of such a bubble may be related to the Xshaped structures centred on the nucleus, but with footpoints at a galactocentric radius r 0 . Thus then would define the midplane flow radius, which may be the boundary of this outflow (Veilleux et al 2021, see also Fig. 21).…”
Section: Motivationmentioning
confidence: 99%
“…We therefore need to investigate the energetics associated with the starburst of NGC 1808 and the outflow. We adopt the isothermal sheet model used by Meléndez et al (2015) and Veilleux et al (2021) to calculate the potential energy required to lift a mass out of the galactic plane,…”
Section: Discussion: Origin Of the Extraplanar Dusty Filamentsmentioning
confidence: 99%
“…The mass-loading factor we find for the dusty outflow in NGC 1808 is therefore typical of starburst galaxies, given the rather large uncertainties on this estimate. For comparison with an AGN-driven outflow, Veilleux et al (2021) find a mass-loading factor in NGC 3079 above 100. The discrepancy between this value and what we find in NGC 1808 is in line with the conclusions of prior work that the AGN in NGC 1808 is rather weak (Salak et al 2018) and energetically not important in driving the observed largescale outflow.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Es-timates of the extraplanar ( > ∼ 1 kpc) FIR emission in edge-on galaxies give similar numbers. For instance, the sum of the FIR fluxes from extraplanar regions around the X-shaped structure in the galaxy NGC 3079 with its SFR≈ 2.6 ⊙ yr −1 (Veilleux et al 2021), results in ∼ 2 × 10 7 SFR in solar units. A similar value ∼ 4 × 10 7 SFR can be inferred from the data for the halo of the galaxy NGC 891 presented by Yoon et al (2021, see their Table 3).…”
Section: 21)mentioning
confidence: 99%